A new weathering indicator from high-temperature magnetic susceptibility measurements in an Argon atmosphere. Issue 3 (6th April 2020) - Liu, Caicai; Wang, Wei; Deng, Chenglong
SUMMARY: Environmental magnetism has become more and more popular because it is inexpensive, rapid and non-destructive. However, the environmental implication of traditional magnetic parameters is changed as the weathering intensity is contrasting. For example, magnetic susceptibility cannot be used as pedogenic index for strongly weathered red soils. Thermal magnetic measurement is a common way to identify magnetic minerals in rocks and sediments. Susceptibility enhancement after a 700 °C heating cycle in an argon atmosphere usually happened for various rocks and sediments. The increase is caused by formation of new magnetite from iron derived from paramagnetic iron-containing minerals. This is similar to pedogenesis or weathering process. The heating process in lab released the residual iron in weatherable iron-containing silicates which has not yet been depleted by contemporary pedogenesis or weathering. This residual iron can be quantified by the amount of susceptibility increase after a heating cycle. A negative correlation between the susceptibility increase after heating and the weathering intensity has been found in high-temperature magnetic susceptibility measurements of several sequences located in different climate zones. Results suggest that the degree of weathering can be estimated for intensely weathered red soils as well as for scarcely weathered loess using the amount of susceptibility change after a 700 °C heating cycle. This study provides new perspectives for developing new weathering and pedoclimate proxies using environmental magnetism.